Analisis Efektivitas Manajemen Rantai Pasok dalam UMKM Kerupuk Singkong Sadariyah di Desa Puhjajar - Ary Permatadeny Nevita; Rachmad Santoso; Hisbulloh Ahlis Munawi (G-Tech: Jurnal Teknologi Terapan, 2024)
Supply chain is a network of several companies that work together to create and deliver a product to the end user. The problem related to SCM in the Sadariyah Cassava Crackers MSME is inventory management of cassava raw materials used to produce these cassava crackers. The aim of this research is to analyze the Supply Chain Management (SCM) used by the Sadariyah Cassava Cracker UMKM in carrying out its production process so that it is effective and efficient so that the objectives that have been set can be met. The method used in this research is a qualitative method by conducting observations and making direct observations of MSME owners. From research it is known that the main problems in MSMEs are the provision of raw materials, storage of raw materials and marketing of products. The solution offered is to establish better communication with suppliers or also add new suppliers who are more cooperative, collaborate with universities to get better storage technology, and improve marketing by participating in product exhibitions events and online marketing.